The Relationship between English Learning Strategies and English Learning Achievement of The Seventh-Grade Student at SMP Negeri 1 SIOMPU Barat - Arsadi, Aditia; Amiruddin, Esa Penilta (Asian Journal of Applied Education (AJAE), 2025)
Appropriate language learning strategies result in improved proficiency and greater self-confidence. The objective of this research was to find out whether there is any significant relationship between English learning strategies and English learning achievement of the seventh-grade student At SMP Negeri 1 Siompu Barat. The research design was quantitative method. Questionnaire and test were the instruments of the study. The sample of the research was 30 seventh-grade students at SMP Negeri 1 Siompu Barat. The findings showed there was no relationship between English learning strategies and English learning achievement of the seventh-grade student at SMP Negeri 1 Siompu Barat.